2013
DOI: 10.1007/s00439-013-1270-y
|View full text |Cite|
|
Sign up to set email alerts
|

Hierarchical modeling identifies novel lung cancer susceptibility variants in inflammation pathways among 10,140 cases and 11,012 controls

Abstract: Recent evidence suggests that inflammation plays a pivotal role in the development of lung cancer. In this study, we used a two-stage approach to investigate associations between genetic variants in inflammation pathways and lung cancer risk based on genome-wide association study (GWAS) data. A total of 7,650 sequence variants from 720 genes relevant to inflammation pathways were identified using keyword and pathway searches from Gene Cards and Gene Ontology databases. In Stage 1, six GWAS datasets from the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…This polymorphism has also been linked to idiopathic pulmonary fibrosis, a disease associated with increased risk of developing lung cancer (Wang et al, 2009). It is also the most studied polymorphism of the TERT gene, as it was described in several previous studies (Chen et al, 2010(Chen et al, , 2012Miki et al, 2010;Wang et al, 2010;Bae et al, 2012;Brenner et al, 2013;Myneni et al, 2103). This polymorphism was reported associated not only with lung cancer (Chen et al, 2010(Chen et al, , 2012Miki et al, 2010;Wang et al, 2010;Bae et al, 2012;Brenner et al, 2013;Myneni et al, 2103), but also with other types of cancer (Wang et al, 2003;Carpentier et al, 2007;Hunter et al, 2007;Sagoo et al, 2009;Savage et al, 2007;Yeager et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This polymorphism has also been linked to idiopathic pulmonary fibrosis, a disease associated with increased risk of developing lung cancer (Wang et al, 2009). It is also the most studied polymorphism of the TERT gene, as it was described in several previous studies (Chen et al, 2010(Chen et al, , 2012Miki et al, 2010;Wang et al, 2010;Bae et al, 2012;Brenner et al, 2013;Myneni et al, 2103). This polymorphism was reported associated not only with lung cancer (Chen et al, 2010(Chen et al, , 2012Miki et al, 2010;Wang et al, 2010;Bae et al, 2012;Brenner et al, 2013;Myneni et al, 2103), but also with other types of cancer (Wang et al, 2003;Carpentier et al, 2007;Hunter et al, 2007;Sagoo et al, 2009;Savage et al, 2007;Yeager et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a number of case-control studies have suggested that rs2736100 in the TERK gene is associated with the risk of lung cancer (Chen et al, 2010(Chen et al, , 2012Miki et al, 2010;Wang et al, 2010;Bae et al, 2012;Brenner et al, 2013;Myneni et al, 2103). The telomerase reverse transcriptase (TERT) gene is located on chromosome 5 (locus 5p15.33) and synthesizes the TTAGGG DNA sequences onto the ends of chromosomes in cooperation with other proteins of the core telomerase complex (e.g., telomerase RNA component [TERC] and dyskerin [DKC1]).…”
mentioning
confidence: 99%
“…Associations with cancers affecting skin (20), lung (21)(22)(23), colon (24), prostate (25), breast (26), testicle (27), bladder (28), and brain (29) were reported. Predisposition to hematologic malignancies such as acute lymphoid leukemia (18), and chronic lymphoid leukemia (30,31), and recently MPN (4-6) were also linked to the TERT locus.…”
Section: Discussionmentioning
confidence: 99%
“…1517 It has been used in areas such as nutrition, occupational health, and genetics. 15,1726 Hierarchical models have also previously been used in evaluating outcomes among HIV-infected adults, but have not been utilized in the context of addressing safety of ARV use during pregnancy. 2729 …”
Section: Introductionmentioning
confidence: 99%